Single-Pulse TMS to the Temporo-Occipital and Dorsolateral Prefrontal Cortex Evokes Lateralized Long Latency EEG Responses at the Stimulation Site - Jarczok, Tomasz A.; Roebruck, Friederike; Pokorny, Lena; Biermann, Lea; Roessner, Veit; Klein, Christoph; Bender, Stephan (Frontiers in Neuroscience, 2021)
Introduction: Transcranial magnetic stimulation with concurrent electroencephalography (TMS-EEG) allows for probing cortical functions in health and pathology. However, is not fully understood how exactly distinct components contribute to compound TMS-evoked potentials (TEP). Late TEP deflections have by some been interpreted as stereotypical responses irrespective of the targeted brain area and linked to non-specific sensory processes. In contrast, we hypothesized that TEPs derived from stimulation of different brain regions would not be uniform and aimed at extracting specific lateralized activity at the stimulation site from compound TEPs containing sensory input. Methods: TMS with concurrent 64-channel EEG was sequentially performed in homologous areas of both hemispheres. One sample of healthy adults received TMS to the dorsolateral prefrontal cortex, another sample received TMS to the temporo-occipital cortex. We analyzed late negative TEP deflections corresponding to the N100 component in motor cortex stimulation. We propose a method to remove unspecific evoked activity that is not systematically lateralized towards the stimulated hemisphere. We expected a maximum always ipsilateral to TMS over the targeted brain region. Results: Over both the temporo-occipital cortex and the dorsolateral prefrontal cortex, there were late negative TEP peaks located in electrodes over the targeted cortex which changed their lateralization depending on the stimulation side. Peak latencies differed between the dorsolateral prefrontal cortex and the temporo-occipital cortex. The analysis of evoked potential components which are systematically lateralized revealed topographical maxima around the respective site of stimulation. Conclusion: TEPs contain site-specific evoked components lateralized towards the stimulated hemisphere which are most likely transcranially evoked and differ in latency depending on the stimulated cortex area. Spatio-temporal overlap with non-specific activity (possibly related to sensory processes associated with TMS) may obscure lateralized site-specific components at the stimulation site. Evoked activity close to the stimulation site reflects different neurobiological processes than potentials measured at remote electrodes.